Perguruan Tinggi Kemaritiman Menghadapi Revolusi Industri 4.0 - Wegig Pratama; Sri Sartini (Majalah Ilmiah Bahari Jogja, 2019)
This paper is aimed to investigate the massive development of Industrial Revolution 4.0 and its challenges in particular for Indonesian Maritime Higher Education by conducting literature review towards some related journals. The result shows that each of Maritime Higher Education in Indonesia should have good readiness and strategies to cope with this era in any reason and condition. Digital-Based Curriculum conversion, upgrading in the learning infrastructure and tools, as well as qualifying human resources are the key points.